LCOS-Based 3 × 3 Folded Wavelength Selective Switch With High-Resolution Spectral - Bing Yu; Yunshu Gao; Genxiang Chen (IEEE Photonics Journal, 2023)
We propose and experimentally verify a 3 × 3 folded wavelength selective switch (WSS) scheme based on liquid crystal on silicon spatial light modulator (LCOS-SLM). This scheme adopts a concise double-layer folded structure that greatly reduced the structural complexity of the WSS system by using the same set of optical elements to accomplish twice beam deflection. The presented WSS is for the C-band, insertion loss is less than 13.2 dB, the spectral resolution is 1 GHz, the bandwidth tuning range is 16.25∼3750 GHz.